Time to Seroconversion in HIV-Exposed Subjects Carrying Protective versus Non Protective KIR3DS1/L1 and HLA-B Genotypes - Tallon, Benjamin J. M.; Bruneau, Julie; Tsoukas, Christos M.; Routy, Jean-Pierre; Kiani, Zahra; Tan, Xianming; Bernard, Nicole F. (PloS one, 2014)
Natural killer (NK) cells play a role in the clearance of viral infections. Combinations of alleles at the polymorphic HLA-B locus and the NK cell surface killer immunoglobulin-like receptor locus KIR3DL1/S1 have been shown to influence time to AIDS in HIV-infected individuals and risk of seroconversion in HIV exposed seronegative (HESN) subjects. Here, we assessed time to seroconversion or duration of seronegative status in a group of 168 HIV exposed individuals, including 74 seroconverters and 94 HESN based on carriage or not of KIR3DL1/S1/HLA-B genotypes previously shown to be associated with protection from infection and/or slow time to AIDS. KIR3DL1/S1 genotyping was performed by sequence-specific primer polymerase chain reaction using two pairs of specific primers for each locus. The MHC class IB locus was typed to four-position resolution to resolve Bw4 and Bw6 alleles and the amino acid present at position 80. KIR3DL1/S1 heterozygotes became HIV infected significantly faster than KIR3DS1 homozygotes. Individuals who carried both KIR3DS1 and Bw4*80I did not remain HIV seronegative longer than those from a control group who were homozygous for HLA-Bw6 and carried no HLA-A locus Bw4 alleles Subjects who were *h/*y+B*57 showed a trend towards slower time to serconversion than those with other KIR3DL1 homozygous and KIR3DL1/S1 heterozygous genotypes. Thus, KIR3DS1 homozygosity is associated with protection from HIV infection while co-carriage of KIR3DS1 and Bw4*80I is not. The requirements for protection from HIV infection can differ from those that influence time to AIDS in HIV infected individuals.